Development of digitized Mandarin paediatric speech perception test materials for Malaysian children - Lim, Elizabeth Shu Jun; Chong, Foong Yen; Quar, Tian Kar; Cila Umat,; Soh, Lee Lee; Leu, Yee Ven; Lim, Hui Woan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Digitized Mandarin paediatric speech perception tests are limited in Malaysia for measuring outcomes among children fitted with amplification devices. Mandarin speech perception tests from other countries may not be suitable to be used in Malaysia due to regional vocabulary differences. In this study, we aim to develop digitized test materials to test Mandarin-speaking preschool children in Malaysia. This is a two-phase cross-sectional study. Phase I is where Mandarin words (n=113) with test item pictures were collated and developed and then tested on 40 Mandarin-speaking children (aged 2;0 to 5;11 years old) with normal hearing. Phase II is where the Mandarin words were digitally recorded and then followed by acoustic analysis, sound quality evaluation, and validation by 20 Mandarin-speaking young adults. In Phase I, a total of 80 of 113 words with high familiarity among children were selected. In Phase II, a total of 192 recorded tokens were selected as finalized test items and all pictures corresponding to these items were validated as suitable representation of the test items. In conclusion, a Mandarin speech perception test which consists of digitally recorded stimuli and pictures has been developed for Mandarin-speaking pre-school children in Malaysia. Objective and subjective evaluations are important to select the best digitized test items and pictures for developing a speech perception test. Future research includes collecting normative data for the test and evaluating the test application in local audiology clinics.